Parents' Self Image in Choosing Education to Support Early Childhood Independence at SPS Sri Lestari Lamongan - Luthfiyah, Alfi Qudsiyyatul; Widodo, Widodo; Yusuf, Ali (IKIP Widya Darma Surabaya, 2025)
Objective: The objective of this study is to explore and validate the self-image of parents at SPS Sri Lestari Lamongan, specifically examining how parental self-image influences their perceptions and decisions to enroll their children early in order to support early childhood independence. Method: The methodology employed is a qualitative research approach, utilizing a case study design to obtain in-depth and descriptive data. Data collection was conducted through interviews and observations with parents whose children attend SPS Sri Lestari, allowing for a comprehensive narrative analysis of their experiences and perspectives. Results: The results indicate that parents at SPS Sri Lestari possess a positive self-image, both personally and toward the institution, which significantly influences their educational choices. This positive self-image shapes their perception of the importance of early education and motivates them to support their children's independence from a young age. Novelty: The novelty of this study lies in its focus on parental self-image as a critical yet underexplored factor in educational decision-making for early childhood. Unlike previous research that primarily addresses parenting styles, parental involvement, or social support, this study highlights the direct impact of parents' self-perceptions on their choices to foster their children's independence through early education. These findings contribute new theoretical insights into the psychological dimensions that underpin parental decisions in early childhood education settings.